EVALUASI PROGRAM PEMBINAAN ANAK TERLANTAR DI SASANA PELAYANAN SOSIAL ANAK “KASIH MESRA” DEMAK - Erni Wigianti; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Abandoned children in Central Java province in 2014 amounted to 66,565, but by 2015 the number has almost doubled to 120,181. Economic reasons and poverty should not be the reason for the placement of children in the institution. Policies that rely on an orphanage system have limited service coverage and are generally less likely to involve parents/families and communities. This study aims to determine the implementation, supporting factors and inhibition of abandoned children's development program in SPSA